PEDAGOGICAL PRACTICE IN MID-LEVEL PROFESSIONAL NURSING EDUCATION - Caroline Silva Morelato Coloni; Verônica Modolo Teixeira; Mirian Christine Olimpio Moreira; Rafaela Piotto; Fernanda dos Santos Nogueira de Góes; Rosangela Andrade Aukar de Camargo (Cogitare Enfermagem, 2016)
The aim of this study was to identify the pedagogical practices developed by professors of mid-level professional education in nursing. A qualitative descriptive study was conducted, with data collection through semi-structured questionnaires, between October and November 2013, in two schools, with the participation of 15 professors/nurses. The frequencies of the responses and content were analyzed in the light of didactic and pedagogical aspects of the literature. Of the respondents, 66.6% were women, with over three years of pedagogical education and healthcare experience. The pedagogical course project was unknown by 46.6%; 53% claimed to elaborate lesson plans; 86.6% reported performing formative assessment; written tests, though, were only applied by 73.3%. With the completion of the study, it was observed that professors generally develop an educational practice devoid of reflection and meaning when they do not participate in the course syllabus. The majority, however, plans the discipline, albeit using misconception on the evaluation of the training.